Fuzzy Rough G-Border and Fuzzy Rough G-Exterior in Fuzzy Rough Topological Groups - Vidhya, D.; Yogalakshmi, T.; Visalakshi, V. (International Journal of Engineering and Technology, 2018)
This paper investigates the concepts of fuzzy rough G-border and fuzzy rough G-exterior. Some interesting properties are established. Also the relationship between them are established.Â